Pressão de radiação : sobre os efeitos das forças de radiação em água - Zanuto, Vitor Santaella (2015)
Among the effects induced by the interaction of radiation with matter, one of the longstanding issues is the definition of the momentum of a traveling photon in a dielectric material. Several formalisms have been developed, and the formulations of Abraham and Minkowski have attracted considerable attention especially due to their controversial nature, the so-called Abraham-Minkowski controversy. Minkowski proposed that the momentum of the photon in a dielectric is proportional to its refractive index, n, and to the photon momentum in the vacuum, p0, that is pM = np0. In contrast, Abraham proposed that the momentum of the photon in the medium is proportional to the momentum in the vacuum and inversely proportional to the refractive index of the medium, such that pA = p0=n. There is no direct method for answering this question yet. However, the passage of a photon through a medium exerts a force, causing a radiation pressure on this medium, that has already been studied for a long time. This work presents a study on the effects of forces induced by radiation at dielectric materials interfaces, specifically at the air/water interface. It provides further advancements in trying to define the real photon momentum in dielectric medium and how the force is generated in the medium. It was used an adapted Photothermal Mirror setup and evaluated the surface deformation of water in diferent configurations of the experimental arrangement. In these arrangements, the laser beam passes through the interface air ! water, water ! air and air ! water ! air (double excitation). It is considered changes in the radial dimensions of the incident beam and we look at what was said to be an experimental evidence that agrees with the prediction of Abraham. All experimental results are compared with numerical models using the Finite Element Method to understand the contributions of radiation forces acting on the surface and in the water volume